The Flouting of Grice’s Conversational Maxims in Pirates of the Caribbean 1-5 - Krismona Apriyani; Thomas Joko Priyo Sembodo (Universitas Gadjah Mada, 2020)
This research is aimed to investigate maxim floutings uttered by the pirate characters in Pirates of the Caribbean movie series. The goals of this research are to identify and classify the maxim flouting within the movie series, to describe how the pirate characters flout the Grice’s maxim, and also to discover the purpose of the maxim flouting itself. Qualitative and quantitative methods are used to analyze the data. The result shows that there are 39 cases of maxim flouting with 4 cases (10.3%) of flouting the maxim of Quantity, 13 cases (33.3%) of flouting the maxim of Quality, 16 cases (41.0%) of flouting the maxim of Relation, and 6 cases (15.4%) of flouting the maxim of Manner. The pirates tend to give too much information, simply say something which does not represent what they think by using: metaphor, irony, sarcasm, and hyperbole, give irrelevant answers, and also give ambiguous answers. There are several purposes of maxim flouting found in this movie series. They are: insulting, giving warning, challenging other characters, boasting about oneself, telling about facts, informing plans, convincing, expressing seriousness, demanding respect, expressing insincerity, expressing love, expressing disappointment, giving advice, expressing happiness, creating fear, creating humor, and avoiding making others sad.